Delusions of Invulnerability : Wisdom and Morality in Ancient Greece, China and Today. - Lloyd, G. E. R. (Classical inter/faces., 2013)
How were the aims of philosophy and the responsibilities of philosophers conceived in ancient Greece and China? How were the learned elite recruited and controlled; how were their speculations and advice influenced by the different types of audiences they faced and the institutions in which they worked? How was a yearning for invulnerability reconciled with a sense of human frailty? In each chapter of this fascinating analysis ancient Greek and Chinese ideas and practices are used as a basis for critical reflections on the predicaments we continue to face today, with a particular focus on the.